Activities of Local Authority in the Uzbek SSR (1927-1930) - Sodikhov, Furkat (International Journal on Integrated Education, 2023)
This article analyzes the activities of local governments and changes in the electoral law as a result of the adoption of the Constitution of the Uzbek SSR, as well as problems in the activities of local governments and measures taken by the Soviet government to prevent them.